Comprehensive Strategies for Targeting Abdominal Obesity in Diabetes - Jacobson, Anne (MD Conference Express, 2011)
Type 2 diabetes mellitus (T2DM) is a progressive disease that is characterized by declining β-cell function, insulin resistance, poor glycemic control, abdominal fat accumulation, and increased risk of cardiovascular disease (CVD). Controlling obesity is particularly challenging for patients with T2DM, given that many standard T2DM medications are associated with weight gain.